O DISCURSO INTOLERANTE RACIAL NA POLÍTICA BRASILEIRA: UMA ANÁLISE SEMIÓTICA - Goiz, Juliana de Almeida (Caderno Seminal, 2017)
É socialmente denominado como intolerância o ato de depreciar uma pessoa em virtude de sua etnia, orientação política, sexual, religiosa, dentre outros. Há diversos discursos intolerantes, no entanto, para este estudo, selecionamos o discurso intolerante racial, que é caracterizado pela intolerância ao etnicamente diferente, mais especificamente, o negro. Nosso corpus científico é composto por um recorte verbal de um noticiário divulgado do ano de 2013 envolvendo afirmações de caráter racista do Deputado Federal Pr. Marco Feliciano, que na época, presidia a Comissão de Direitos Humanos e Minorias da Câmara dos Deputados no Brasil. Este estudo tem como objetivo (i) analisar a construção narrativa dos discursos de intolerância racial, (ii) apresentar o percurso das paixões neste tipo de discurso e (iii) reconhecer, bem como discernir esta tipologia discursiva a fim de desconstruí-la. Para isso, fundamentamos nossos estudos na Teoria Semiótica Discursiva. A bibliografia que consistirá em analisar a formação dos valores do sujeito intolerante será a semiótica das paixões nos discursos de segregação e a análise do percurso gerativo de sentido em seus três patamares: nível fundamental, nível narrativo e nível discursivo.. Nossa hipótese inicial é que os discursos de intolerância racial são, sobretudo, apaixonados e suas estruturas discursivas constituem um todo de sentido. A relevância deste estudo está pautada na necessidade de se problematizar o racismo a fim de desmistificá-lo. It is socially termed as intolerance the act of belittling a person because of their religion, ethnicity, orientation political, sexual, among others. There are several intolerant discourses; however, for this study, we selected the religious and racial intolerant discourse, which is characterized by the intolerance intended, more specifically, to non-christian black people. Our scientific corpus consists of a news report published in 2013 involving religious and racial intolerant statements of Congressman Pr. Marco Feliciano, who, at that time, was the president of the Commission on Human Rights and Minorities of the Chamber of Deputies in Brazil. This clipping has been chosen because of its social recognition as a intolerant speech, the high level of dissemination in different press and media vehicles, and the social contradiction existent between exercising a political office, which aims to represent the social minorities and issues intolerant speeches at the same time. This study aims to (i) analyze the narrative construction of religious and racial intolerant discourses, (ii) present the process of passions in this kind of discourse and (iii) recognize, as well as discern, this discursive typology in order to deconstruct it. In order to do that, we have based our studies in the Discursive Semiotic Theory. The bibliography that will consist of analyzing the formation of the values of the intolerant subject will be the semiotics of the passions in the discourses of segregation and the analysis of the generative path of meaning in its three levels: fundamental level, narrative level and discursive level. The theoretical framework to be used is based on the studies by Barros (1990, 1995, 2005, 2008, 2011); Fiorin (1988, 1992); Greimas (1970, 1976, 1983); Greimas e Fontanille (1993); Fontanille e Zilberberg (2001); Zilberberg (2006). Our initial hypothesis is that the religious and racial intolerant discourses are, above all, passionate and, their discursive structures constitute a whole of meaning. The relevance of this study is grounded on the need of problematizing the intolerance religious and racism in order to demystify it.